Pathways to greater government accountability for breaches of their obligations in relation to doping in sport: A legal analysis - David Pavot (Frontiers Media S.A., 2023)
The State doping scandal in Russia has highlighted a major discrepancy in the fight against doping in sport: on the one hand, the signatories of the Word Anti-Doping Code (federations, NADO's, etc.) are subject to a very strict regime and incur serious sanctions, while on the other hand, States, when they massively violate the rules, do not risk very important consequences in international law. For example, high ranking officials as well as the Russian state apparatus have not been affected with a few exceptions such as the Moscow antidoping laboratory. The aim of this opinion paper is to present a reflection on the different avenues that could be envisaged to make governments more accountable, especially as work is underway on the topic. The development of a true government accountability regime would allow the system to be more balanced.